2018
DOI: 10.1029/2018gl077804
|View full text |Cite
|
Sign up to set email alerts
|

Melting Inside the Tibetan Crust? Constraint From Electrical Conductivity of Peraluminous Granitic Melt

Abstract: Magnetotelluric and seismological studies suggested the presence of partial melts in the middle to lower Himalaya-Tibetan crust. However, the melt fractions inferred by previous work were based on presumed electrical conductivity of melts. We performed measurements on the electrical conductivity of peraluminous granitic melts with 0.16-8.4 wt % H 2 O (the expected compositions in the Tibetan crust) at 600-1,300°C and 0.5-1.0 GPa. Peraluminous melt exhibits lower electrical conductivity than peralkaline melt at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 61 publications
(149 reference statements)
4
35
0
Order By: Relevance
“…Accounting for temperature, pressure, and water content effects altogether, granitic melt conductivity σ f can then be calculated according to a generalized formula constrained by experimental data (X. Guo et al, 2018): lefttruelogσf=3.205±0.0670.102±0.016w4228.5±83.2354.7±18.1w+694.6±37.8PnormalT where w is the water content (in wt.%), P is the pressure (in GPa), and T is the temperature (in K). J. Chen et al (2018) developed a similar empirical model for the estimation of the melt/fluid conductivity using the Arrhenius equation.…”
Section: Rheology Constraints From Conductivity Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Accounting for temperature, pressure, and water content effects altogether, granitic melt conductivity σ f can then be calculated according to a generalized formula constrained by experimental data (X. Guo et al, 2018): lefttruelogσf=3.205±0.0670.102±0.016w4228.5±83.2354.7±18.1w+694.6±37.8PnormalT where w is the water content (in wt.%), P is the pressure (in GPa), and T is the temperature (in K). J. Chen et al (2018) developed a similar empirical model for the estimation of the melt/fluid conductivity using the Arrhenius equation.…”
Section: Rheology Constraints From Conductivity Modelmentioning
confidence: 99%
“…Accounting for temperature, pressure, and water content effects altogether, granitic melt conductivity σ f can then be calculated according to a generalized formula constrained by experimental data (X. Guo et al, 2018): where w is the water content (in wt.%), P is the pressure (in GPa), and T is the temperature (in K). J.…”
Section: Melt Fraction Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, geophysicists have shown that the high‐conductivity anomalies in the Earth's lithosphere can be caused by the presence of water in nominally anhydrous minerals (Dai & Karato, 2014; Karato, 2019; H. Y. Liu et al, 2019; Wang et al, 2006; Yang et al, 2011), interconnected aqueous fluids (Amiguet et al, 2012; X. Z. Guo et al, 2015; Li et al, 2018; Manthilake et al, 2015, 2016; Shimojuku et al, 2014; Sinmyo & Keppler, 2017), partial melting (Freitas et al, 2019; Gaillard, 2005; X. Guo et al, 2018; Laumonier et al, 2015, 2017; Maumus et al, 2005; H. W. Ni et al, 2011), and interconnected secondary high‐conductivity phases (Bagdassarov et al, 2009; Glover et al, 1996; Kawano et al, 2012; Manthilake et al, 2016; Wang et al, 2013; Zhang & Yoshino, 2016). Despite multiple interpretations for the high‐conductivity anomalies in the deep Earth, the practical origin in a certain geological environment can be constrained based on the MT and seismic data.…”
Section: Introductionmentioning
confidence: 99%
“…Despite multiple interpretations for the high‐conductivity anomalies in the deep Earth, the practical origin in a certain geological environment can be constrained based on the MT and seismic data. Generally, low seismic waves are also a characteristic of a deep region with a high‐conductivity anomaly (Chen et al, 2009; Gonzalez‐Castillo et al, 2019; X. Guo et al, 2018; Naif et al, 2013). Although aqueous fluids and melts can reconcile the observed anomalous electrical conductivity and seismic waves (Marquis & Hyndman, 1992; Naif et al, 2013), aqueous fluids are more stable than melts in regions with a low geothermal gradient.…”
Section: Introductionmentioning
confidence: 99%